PMO-203 Direct gastric puncture and gastropexy (Freka® Pexact) insertion technique for percutaneous endoscopic gastrostomy reduces peristomal infection rates compared with standard pull-through insertion in patients with head and neck cancer. (28th May 2012) - Disney, B R; Nizamuddin, M; Tanajura, A; Anderson, M; Lewis, M
Abstract : Introduction: Patients with head and neck cancer often have a percutaneous endoscopic gastrostomy (PEG) inserted to provide nutritional support while undergoing treatment. The standard pull-through PEG technique is associated with a high incidence of peristomal infection. This is thought to be a result of pulling the PEG through the oral cavity which may be colonised with bacteria. In addition there is the risk of tumour seeding at the PEG site with this method. In our institution, such patients now have an endoscopical controlled introducer PEG (Freka ® Pexact) with dual gastropexy inserted which avoids passage of the bumper through the oral cavity. We aimed to compare peristomal infection rates between the two methods of PEG insertion. Methods: We carried out a retrospective audit of PEG insertions in patients with head and neck cancer. Patients were identified using the ADAM ® medical documentation system (Fujinon Europe GmbH, Willich, Germany) and the Nutrition team logs. Complications, peristomal infection and 30-day mortality were documented after review of case notes and liaison with Community Nutrition Nurses. Results: A standard pull-through PEG (16F Corflo ®, Merck, UK) was inserted in 13 patients and 30 patients had a Freka ® Pexact 15F (Fresenius Kabi, Germany) inserted. Of the Pexact group 76.7% were male (n=23); 84.6% (n=11) of the standard group were male. The mean age of patients was 58 years (range 35–81) in the Pexact group and 61 years (range 35–78) in the standard PEG group. Prophylactic antibiotics were prescribed to 83.3% (n=25) in the Pexact group compared with 100% (n=13) of the standard pull-through PEG group. In the standard PEG group 69.2% (n=9) developed peristomal infection compared with 36.7% (n=11) in the Pexact group. Immediate complications occurred in 15.4% (n=2) in the standard group and in none of those in the Pexact group. There were no deaths in either group at 30 days. Conclusion: The introduction of the direct gastric puncture and gastropexy technique led to a significant reduction of peristomal infections in patient with head and neck cancer. This new technique is well tolerated by patients. Competing interests: None declared.